(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Preeclampsia is a multisystem hypertensive disorder of pregnancy that remains one of the leading causes of maternal and perinatal morbidity and mortality worldwide. Early identification of women at high risk is essential for improving obstetric outcomes. Recent advances in molecular medicine have introduced novel endothelial and angiogenic biomarkers, including endothelial nitric oxide synthase (NOS3), placental growth factor (PlGF), soluble fms-like tyrosine kinase-1 (sFlt-1), and soluble endoglin (sEng). The present study proposes a diagnostic algorithm integrating clinical risk assessment, Doppler ultrasonography, and laboratory biomarkers for the early prediction and stratification of preeclampsia risk. The combined evaluation of angiogenic imbalance and endothelial dysfunction markers significantly increases diagnostic accuracy compared to traditional clinical criteria alone. Implementation of such an algorithm in routine obstetric practice may enhance early detection and allow timely preventive interventions.